A Survey of Soft Robot Actuation, Sensing, and Application - Abdulshaheed, Areej Ghazi; Mahdi, Suhair Ghazi (Newinera Publisher, 2025)
Because of their fundamentally high adaptability, high compliance, excellent flexibility, and safe and natural interactive features, soft robotics technologies are pointing the path toward robotic capabilities that are essential for a wide range of applications, including manufacturing, manipulation, gripping, human-machine interaction, locomotion, and more. Soft robots are incredibly versatile and lightweight, making them ideal for interacting with delicate things and navigating unstructured spaces. Soft robots have not yet reached their full potential, though; in many aspects, including manipulation and movement, nature still possesses considerably greater sophistication. Future research should concentrate on comprehending the concepts behind the design and operation of soft robots in order to identify what constrains the way they function and impedes their transfer from the lab to real-world settings. Through an analysis of the operation of sophisticated actuation and sensor technologies, this paper offers a current overview of the area. Lastly, examples of the different soft actuators and possibilities for future development are reviewed, along with a number of prospective implementations.